(untitled) (Urdimento: Revista de Estudos em Artes Cênicas, 2020)
Taking a critique of mere architectural conceptions of theatrical spaces as its starting point, this paper discusses different ways of undermining the proscenium stage as what can be called a dispositif or apparatus of perception. It discusses up to which point the perturbation, negation and disaffirmation of the italian stage, carried out through different spatial conception by the performances analysed in this paper, can serve to exemplify Agamben’s afirmation that the profanation of a (political) dispositif highlights the point of ungovernability that exists at the beginning and the end of any political praxis.